Valuation and Accounting for Inflation and Foreign Exchange - HUGHES, JOHN; LIU, JING; ZHANG, MINGSHAN (Journal of Accounting Research, 2004)
ABSTRACT Inflation and foreign exchange raise new issues with respect to accounting representations of equity value. For example, inflation creates an earnings illusion as an artifact of the mismatching of expenses based on allocations of historical costs with current revenues in determining earnings. This mismatching distorts mappings of aggregate earnings and book values into equity value such that value‐relevant information is lost. In this article we consider the consequences of inflation and foreign exchange accounting policies, including those contained in accounting standards, on the value relevance of bottom‐line accounting numbers. Policies are identified that achieve efficient accounting in the sense that aggregate (comprehensive) earnings and book values are sufficient for an accounting representation of equity value. The linear relations that emerge provide predictions on capitalization coefficients that help explain results of empirical inquiries. As well, our analysis provides a theoretical foundation for policies contained in accounting standards that contributes to the resolution of controversies such as that concerning foreign exchange accounting.